Through no fault of their own? the fate of those who have never heard - Crockett, William V.; Sigountos, James George, 1956- (Grand Rapids, MI Baker, 1991)
Includes bibliographical references and indexes.
Keywords: Salvation outside the church; Christianity and other religions; Universalism